(untitled) - Wilson, Lonnie (New York, 2010)
This real-world resource offers proven solutions for implementing lean manufacturing in an enterprise environment, covering the engineering and production aspects as well as the business culture concerns. Filled with detailed examples, the book focuses on the rapid application of lean principles so that large, early financial gains can be made. How to Implement Lean Manufacturing explains Toyota Production System (TPS) practices and specifies the distinct order in which lean techniques should be applied to achieve maximum gains. Global case studies illustrate successes and pitfalls of lean manufacturing initiatives.
Keywords: Sản xuất tinh gọn,Lean manufacturing